Geoengineering, Theology, and the Meaning of Being Human - Clingerman, Forrest (Zygon, 2014)
Because of the lack of a meaningful international response to global warming, geoengineering has emerged as a potential technological response to climate change. But, thus far, little attention has been given to how religion impacts our understanding of geoengineering. I defend the need to incorporate theological reflection in the conversation of geoengineering by investigating how geoengineering proposals contain an implicit anthropology. A significant framework for our assessment of geoengineering is the balance of human capability and fallibility—a balance that is at the center of theological and religious interpretations of the meaning of the human condition. Similarly, geoengineering challenges our past understandings of theological anthropology.